Atlas of Cutaneous Lymphomas Classification and Differential Diagnosis - Carter, Joi B.; Goyal, Amrita; McDivitt Duncan, Lyn.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The integration of clinical findings, laboratory results, and disease progression is critical for the diagnosis and treatment of patients with skin lymphoma. This atlas includes numerous clinical and histological images with diagrams, tables, and text describing each type of lymphoma in the current cutaneous classification scheme, which includes information on the recent classification scheme for cutaneous lymphoma published by the World Health Organization and the European Organization for Research and Treatment of Cancer Cutaneous Lymphoma Group.   Atlas of Cutaneous Lymphomas: Classification and Differential Diagnosis includes chapters on synonyms, clinical features (presentation, prognosis, and treatment), laboratory findings (histopathology, immunophenotype, and molecular), differential diagnosis, and presentation of clinical cases for each diagnostic entity. In addition, chapters are included on T-cell lymphomas, B-cell lymphomas, ancillary techniques including immunohistochemistry and molecular tests, and a glossary of terms. This book will help clarify the classification of cutaneous lymphoma and will serve as a useful tool for physicians involved in the diagnosis and treatment of patients with cutaneous lymphoma.
History and Genesis of the EORTC/WHO Lymphoma classification -- Beyond the routine processing: immunohistochemistry, in situ hybridization and genetic analysis -- Mycosis fungoides -- MF variants and subtypes -- Folliculotropic MF -- Pagetoid reticulosis -- Granulomatous slack skin -- Sézary syndrome -- Adult T-cell leukemia/lymphoma -- Primary cutaneous CD30+ lymphoproliferative disorders -- Primary cutaneous anaplastic large cell lymphoma -- Lymphomatoid papulosis -- Subcutaneous panniculitis-like T-cell lymphoma -- Extranodal NK/T-cell lymphoma, nasal type -- Primary cutaneous peripheral T-cell lymphoma, rare subtypes -- Primary cutaneous CD8-positive aggressive epidermotropic cytotoxic T-cell lymphoma -- Primary cutaneous gamma-delta T-cell lymphoma -- Primary cutaneous CD4-positive small/medium T-cell lymphoma -- Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) -- Primary cutaneous follicle centre lymphoma -- Primary cutaneous diffuse large B-cell lymphoma, leg type -- Intravascular large B-cell lymphoma -- Blastic Plasmacytoid Dendritic Cell Neoplasm -- Clinical mimics of T cell lymphomas -- Clinical mimics of B cell lymphomas -- Histopathologic mimics of cutaneous T cell lymphoma -- Histopathologic mimics of cutaneous B cell lymphoma -- Glossary.
Keywords: Dermatology; Oncology .; Pathology; Dermatology; Oncology; Pathology